Bidirectional approach of Punica granatum natural compounds: reduction in lung cancer and SARS-CoV-2 propagation - Md. Abul Barkat; Afreen Fatima; Bushra Riaz; Mohd. Zaheen Hassan; Tanveer Ahamad; Abdulkareem A. Alanezi; Harshita Barkat; Afaf F. Almuqati; Yahya I. Asiri; Sahabjada Siddiqui (BMC Complementary Medicine and Therapies)
Abstract The spreading of COVID-19 has posed a risk to global health, especially for lung cancer patients. An investigation is needed to overcome the challenges of COVID-19 pathophysiology and lung cancer disease. This study was designed to evaluate the phytoconstituents in Punica granatum peel (PGP), its anti-lung cancer activity, and in silico evaluation for antiviral potential. GC–MS technique was used to detect the phytoconstituents. Cytotoxicity was analyzed using MTT dye, followed by apoptosis, ROS generation, and cell cycle phase detection in human lung cancer cells (A549). The glide module of Maestro software was used to investigate the molecular-docking interaction of the constituents against main protease (Mpro) and papain-like protease (PLpro) of SARS-CoV-2. GROMACS 2023.2 was utilized to evaluate the complex stability. A total of nineteen phytocomponents were detected in the PGP extract through GC–MS analysis. PGP has shown a potential to reduce lung cancer cell proliferation while evading normal cell death. PGP induced apoptosis by arresting cells in the G0/G1 phase and generating ROS. A total of six and eight phytocomponents had a high affinity for PLpro and Mpro proteins, respectively. The top docked complex, ethyl 5-oxo-2-pyrrolidinecarboxylate, with PLpro and Mpro proteins, showed likely stable interaction throughout 100 ns simulation. This finding raises the possibility of top-eight hits (docking score ≥ -1.0 kcal/mol) preventing SARS-CoV-2 severity. The phytoconstituents exhibited orally active drugs with no more than one violation and drug-likeness activity. The PGP phytoconstituents are suggested to be dual agents for lung cancer and SARS-CoV-2 pathogenesis. Graphical Abstract